Influence of porous substrate on copper based oxygen carrier efficiency for chemical-looping combustion - van Garderen, Noemie (2014)
The efficiency of impregnated redox material and its cycling behaviour by tailoring macro- to mesoporosity of different support compositions for fluidized-bed application was investigated. Supports are composed of clay and diatomite, alumina, alumina and diatomite, alumina diatomite and silica. The porous supports were impregnated with 1.5 M copper nitrate trihydrate and calcined at 850 °C. Higher presence of copper has been determined on samples composed of higher specific surface area and larger pore size distribution. Presence of CuO and Cu2O phases were obtained in silica based samples (clay, diatomite or silica nanoparticles), whereas CuAl2O4 dominated in samples with high alumina content. Reaction rate during reduction increased with silica, while total conversion was reduced. Highest conversion was obtained for alumina samples because of the aggregation of copper on pure silica surfaces. It is assumed that after infiltration of 10 wt.% copper phase, surface chemistry is of great importance compared to pore size. Wet impregnation had no effect on attrition resistance.